Mechanical loading disrupts osteocyte plasma membranes which initiates mechanosensation events in bone. Issue 2 (11th August 2017) - Yu, Kanglun; Sellman, David P.; Bahraini, Anoosh; Hagan, Mackenzie L.; Elsherbini, Ahmed; Vanpelt, Kayce T.; Marshall, Peyton L.; Hamrick, Mark W.; McNeil, Anna; McNeil, Paul L.; McGee‐Lawrence, Meghan E.
ABSTRACT: Osteocytes sense loading in bone, but their mechanosensation mechanisms remain poorly understood. Plasma membrane disruptions (PMD) develop with loading under physiological conditions in many cell types (e.g., myocytes, endothelial cells). These PMD foster molecular flux across cell membranes that promotes tissue adaptation, but this mechanosensation mechanism had not been explored in osteocytes. Our goal was to investigate whether PMD occur and initiate consequent mechanotransduction in osteocytes during physiological loading. We found that osteocytes experience PMD during in vitro (fluid flow) and in vivo (treadmill exercise) mechanical loading, in proportion to the level of stress experienced. In fluid flow studies, osteocyte PMD preferentially formed with rapid as compared to gradual application of loading. In treadmill studies, osteocyte PMD increased with loading in weight bearing locations (tibia), but this trend was not seen in non‐weight bearing locations (skull). PMD initiated osteocyte mechanotransduction including calcium signaling and expression of c‐fos, and repair rates of these PMD could be enhanced or inhibited pharmacologically to alter downstream mechanotransduction and osteocyte survival. PMD may represent a novel mechanosensation pathway in bone and a target for modifying skeletal adaptation signaling in osteocytes. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:653–662, 2018.